TC4 titanium alloy preformed blank, TC4 titanium alloy plate with basket structure and preparation method of TC4 titanium alloy plate
By using powder metallurgy preforms and a single-fire rolling process, the problem of poor microstructure uniformity of TC4 plates was solved, enabling the preparation of high-performance wide-width TC4 plates, improving yield and reducing production costs, and meeting the application needs of the aerospace field.
Patent Information
- Application Number
- CN202511185040.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional forging processes produce TC4 plates with poor microstructure uniformity and low yield, making it difficult to meet the high-performance requirements of the aerospace industry.
A TC4 titanium alloy preform with a dual-state structure was formed by using a powder metallurgy preform preparation method, which involves hydrogenation and dehydrogenation powder preparation, plasma rotating electrode atomization treatment, and three-step hot isostatic pressing. The preform was then combined with one-fire rolling and composite heat treatment to prepare a TC4 titanium alloy plate with a basket-like structure.
It has enabled the preparation of high-performance, highly uniform wide-width TC4 sheets, simplified the process, improved the yield, reduced production costs, and met the application requirements of the aerospace field.
Smart Images

Figure CN120984887A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of titanium alloy processing, and relates to a TC4 titanium alloy preform, a TC4 titanium alloy plate with a basket weave structure and a preparation method thereof, in particular to a high-strength and high-toughness wide TC4 plate preparation method through single-stand rolling of a powder metallurgy preform. BACKGROUND
[0002] In the field of aerospace, with the continuous rise of the overall level of industry, the demand for personalized preparation of TC4 plates gradually emerges, and the preparation mode is also changing from the traditional general process to the personalized preparation mode of special plates. Under this background, the key performance indicators such as strength and toughness of aerospace-grade plates are steadily improving. At present, TC4 plates are mainly prepared by the following two process paths: one is to obtain a plate blank by means of forging breakdown after 3 times of VAR furnace casting into ingots; the other is to adopt EB furnace pouring flat blank. After the plate blank is prepared, it still needs to be subjected to multiple passes of reciprocating and cross-rolling to finally become a finished product.
[0003] The traditional forged blank has dendritic segregation phenomenon and poor organization uniformity, and has problems such as difficulty in controlling the flaw detection qualified rate, residual stress and plate shape of aerospace-grade titanium alloy plates, and the production mode has a long process flow and low yield. According to statistics, the yield of domestic titanium material production enterprises from ingot casting to finished product plate of 3-6mm (thickness) x 1400-2000mm (width) is less than 60%. Although the EB furnace pouring flat blank shortens the process flow to a certain extent, the as-cast organization cannot meet the requirements of anisotropy and organization uniformity of the plate through fine control rolling and controlled cooling methods. Limited by ingot casting, plate blank multi-pass rolling and intermediate heat treatment, etc., there may be problems such as organization non-uniformity, plate warpage, residual stress and ultrasonic flaw detection in the long process flow, and the performance qualified rate after finishing is also a technical problem restricting the application of titanium metal.
[0004] Although the existing patent technologies have proposed some improvement schemes, they still have their own limitations. For example, CN120079718A discloses a method for one-pass rolling of thin-gauge super-wide TC4 titanium alloy plate, and in order to ensure the surface quality, the method adopts surface explosion to composite a layer of pure titanium plate, which has high production environmental protection requirements. Secondly, the method adopts reversing rolling, which has great difficulty in on-site process execution and unstable production quality. CN117066281A discloses a hot rolling preparation method of TC4 titanium alloy single plate, which adopts three-pass rolling to prepare TC4 plate, and the process flow is long. CN115971249A discloses a preparation method of super-thin TC4 titanium alloy plate, which adopts multi-pass rolling breakdown method for ingot casting, and the plate blank organization control level is poor, which is difficult to meet the requirements of high organization uniformity of aerospace grade.
[0005] In summary, the current TC4 plate preparation technology still faces many challenges in pursuing high performance, high pass rate and process stability, and a low-cost preparation process that can simplify the process flow, improve the yield and ensure uniform product performance is urgently needed. SUMMARY
[0006] The technical problem to be solved by the present application is the poor uniformity of the microstructure of the cast blank prepared by the traditional forging process.
[0007] To achieve the above application purposes, the technical solutions adopted by the present application are as follows: In a first aspect, the present application provides a preparation method of a TC4 titanium alloy preform: after pretreatment, TC4 recycled waste is powderized by hydrogenation and dehydrogenation, and then treated by plasma rotating electrode atomization to obtain alloy powder with oxygen content ≤0.15wt%; the alloy powder is treated by three-step hot isostatic pressing to obtain a TC4 titanium alloy preform with a duplex structure; The three-step hot isostatic pressing includes: in the first stage, the temperature is raised to 150-250℃ at a rate of 5-10℃ / min, and the vacuum degree is ≤1×10 -2 Pa; in the second stage, the temperature is raised to 400-500℃ at a rate of 5-10℃ / min, and the vacuum degree is ≤4×10 -2 Pa; in the third stage, the temperature is raised to 920-980℃ at a rate of 3-6℃ / min, a static pressure of 100-140MPa is applied, and the temperature and pressure are maintained for 120-180min. The TC4 titanium alloy preform has a density ≥99.8%, the size of primary equiaxed alpha phase is ≤10μm, and the alpha lamella spacing is ≤10μm.
[0008] In the above preparation method, the pretreatment includes: after cleaning the TC4 recycled waste with a 3% HNO3 solution and a 1% HF solution, the waste is annealed under vacuum at 600-800℃, and then cut or broken into small pieces of 3-15mm.
[0009] In the above preparation method, the TC4 recycled waste includes one or more of machining chips, molding excess material, and metallurgical waste.
[0010] In the above preparation method, the hydrogenation and dehydrogenation powdering includes: placing the small pieces in a sealed reactor, introducing high-purity hydrogen gas to a pressure of 0.3-2.8MPa, hydrogenating at 400-800℃ for 8-18h, then crushing and sieving to obtain hydride powder; the hydride powder is placed in a vacuum environment with a vacuum degree ≤10 -2 Pa, dehydrogenated at 650-820℃ for 8-18h, and then cooled to room temperature in vacuum or under inert gas protection, and then treated by plasma rotating electrode atomization to obtain TC4 alloy powder.
[0011] In the preparation method, the particle size of the TC4 alloy powder is 50-150 μm.
[0012] In the preparation method, the content of elements other than oxygen in the TC4 alloy powder meets the requirements of GB / T3620.1.
[0013] In the preparation method, the hot isostatic pressing further comprises: the TC4 alloy powder after the degassing treatment is loaded into a bag cover preheated to 400-450 ℃, and then three-step hot isostatic pressing is performed; after the hot isostatic pressing is completed, the TC4 titanium alloy preform with a duplex structure is obtained by cooling at a cooling rate of ≥10 ℃ / min to below 450 ℃ in an argon environment with a pressure of 45-65 KPa, and then cooling to room temperature in an argon environment with a pressure of 105-135 KPa.
[0014] In the preparation method, the material of the bag cover is pure titanium plate.
[0015] In the preparation method, the wall thickness of the bag cover is 1-3 mm.
[0016] In the preparation method, the size of the bag cover is: length 2000-2200 mm x width 1800-2000 mm x thickness 80-100 mm.
[0017] In a second aspect, the application provides a preparation method of a TC4 titanium alloy plate: a TC4 titanium alloy preform with a duplex structure is prepared by the preparation method of the TC4 titanium alloy preform, and then hot rolling and composite heat treatment are performed to obtain a TC4 titanium alloy plate with a basket weave structure; the basket weave structure is that α lamellas are in short rod shape and α clusters are staggered. In the preparation method, the hot rolling adopts one-fire rolling forming, the preform is heated to a rolling temperature in a gas atmosphere or an electric heating furnace and then rolled out of the furnace, and the rolling direction is along the width direction of the preform; the opening rolling temperature is 40-80 ℃ above the β phase transition point of the preform, the subsequent pass temperature is reduced to the α+β two-phase region, and the finish rolling temperature is ≥700 ℃; the rolling deformation rate distribution principle of the one-fire rolling is that the deformation ratio of the β phase region to the α+β two-phase region is 1.1-1.2:1, the total deformation amount is >80%, and the subsequent pass deformation amount is gradually reduced to 10-15%.
[0018] In the preparation method, the one-fire rolling is cooled on a roller bed after the finish rolling pass, and the cooling rate is controlled at 1.5-2.0 ℃ / s.
[0019] In the preparation method, the composite heat treatment is specifically as follows: the rolled plate is heated to 780-820 DEG C and kept for 1-2 hours, and then air-cooled to room temperature; then heated to 470-550 DEG C and kept for 4-8 hours, and then air-cooled to room temperature; and finally, the head and tail are sawed off to obtain the TC4 titanium alloy plate with the basket weave structure.
[0020] In a third aspect, the present application provides a TC4 titanium alloy plate with the basket weave structure prepared by the preparation method of the TC4 titanium alloy plate.
[0021] Further, the size of the TC4 titanium alloy plate is 6000-15000 mm in length, 2000-2200 mm in width and 5-10 mm in thickness.
[0022] Further, the mechanical properties of the TC4 titanium alloy plate are as follows: the longitudinal tensile strength is greater than or equal to 960 MPa, the yield strength is greater than or equal to 890 MPa, the elongation is greater than or equal to 13%, the reduction of area is greater than or equal to 35%; the transverse tensile strength is greater than or equal to 1000 MPa, the yield strength is greater than or equal to 960 MPa, the elongation is greater than or equal to 11%, the reduction of area is greater than or equal to 35%; the fracture toughness K IC of the T-L direction is greater than or equal to 60 MPa·m 1 / 2 , and the fracture toughness K IC of the L-T direction is greater than or equal to 65 MPa·m 1 / 2 .
[0023] The present application has the following beneficial effects: Different from the conventional method of improving the grade of titanium sponge, reducing the mass fraction of impurities and interstitial atoms and improving the strength and toughness of the TC4 plate, the present application provides a method for preparing a high-performance and high-uniformity wide TC4 plate without the selection of titanium sponge and the control of impurity elements in intermediate alloy, through green low-cost powder metallurgy to prepare a TC4 plate blank, combined with one-fire rolling and composite heat treatment, to realize the preparation of the TC4 plate. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 It is a process control curve diagram for hot isostatic pressing treatment; Figure 2 It is a scanning electron microscope photo of the bimodal structure preform prepared in Example 1; Figure 3 It is a metallographic photo of the basket weave structure TC4 titanium alloy plate prepared in Example 1; Figure 4 It is a scanning electron microscope photo of the bimodal structure preform prepared in Example 2; Figure 5 It is the microstructure of the preform prepared in Comparative Example 1; Figure 6 Microstructure of the finished plate material prepared for Comparative Example 2. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved in the present application clearer, the present application will be further described in detail below in conjunction with embodiments. Unless otherwise defined, all technical terms used herein have the same meanings as understood by those skilled in the art.
[0026] A method for preparing a high-performance and high-uniformity wide-width TC4 titanium alloy plate material, comprising the following steps.
[0027] (1) The TC4 recycled waste is subjected to weak acid cleaning (3% HNO3+1% HF solution) and vacuum annealing at 600-800°C to remove surface impurities. The bulk raw material is cut or broken into small pieces with a relatively uniform size of 3-15 mm to increase the specific surface area of the subsequent hydrogenation reaction and improve the hydrogenation efficiency and uniformity.
[0028] In an embodiment of the present application, the TC4 recycled waste includes one or more of machining chips (such as turning chips, milling chips), molding excess material (such as forging corner material, casting corner material), and metallurgical waste (such as unqualified ingots, unqualified bars). The TC4 recycled waste is the main source of economy of the method of the present application, and recycling the TC4 recycled waste as a raw material can effectively reduce the production cost.
[0029] (2) The pretreated TC4 raw material is placed in a sealed reactor (usually a vacuum / atmosphere furnace resistant to high temperature and high pressure). High-purity hydrogen (H2) is introduced, and the temperature is heated to a suitable hydrogenation temperature for holding. The hydrogenation reaction causes lattice expansion, resulting in a huge internal stress, making the originally ductile TC4 alloy very brittle (hydrogen embrittlement) and easily crushed.
[0030] In an embodiment of the present application, the hydrogen pressure is usually in the range of 0.3-2.8 MPa, and the pressure affects the hydrogen absorption rate and the final hydrogen content. For TC4 alloy, the hydrogenation temperature is usually in the range of 400-800°C, and a temperature that is too low will result in a slow hydrogenation speed, and a temperature that is too high may cause grain coarsening or local melting. The holding time is 8-18 h, so that the hydrogen gas can fully diffuse into the alloy and react with titanium to form titanium hydride (mainly TiH2, and aluminum and vanadium hydrides or solid solutions).
[0031] (3) The brittle TC4 hydride block after hydrogenation is taken out of the reactor. A simple mechanical crushing method is used to crush the brittle hydride into a powder with a desired particle size. The crushed powder is sieved, and the powder meeting the target particle size range (3-15 mm) is separated, and the oversized powder is returned for further crushing.
[0032] (4) The sieved TC4 hydride powder is placed in a vacuum heat treatment furnace for heat preservation and dehydrogenation. The hydride is decomposed and hydrogen is removed, and the powder is restored to the state of titanium alloy (Ti-6Al-4V).
[0033] In an embodiment of the present application, the dehydrogenation is carried out in a high vacuum environment (≤10 -2 Pa), which ensures that hydrogen can be effectively extracted and prevents oxidation. For TC4 alloy, the dehydrogenation temperature must be high enough to drive hydrogen desorption and diffusion, while being lower than the beta transformation temperature (about 995°C for TC4) to avoid excessive grain growth and phase transformation. Too high a temperature is also prone to introduce impurities such as oxygen and nitrogen. Therefore, the dehydrogenation temperature is usually in the range of 650-820°C. The heat preservation time is 8-18h, which allows hydrogen to be fully desorbed and diffuse out of the powder.
[0034] (5) After dehydrogenation, the powder is cooled to room temperature under vacuum or inert gas (such as argon) protection to prevent oxidation of the hot powder, and then subjected to plasma rotating electrode atomization treatment to obtain TC4 alloy powder. The powder is subjected to chemical composition detection, including the content of main elements (Ti, Al, V) and the content of key impurity elements (O, H, N, C, Fe). The TC4 alloy powder has a particle size of 50-150μm, an oxygen content of ≤0.15wt%, and the remaining elements meet the requirements of GB / T3620.1.
[0035] In an embodiment of the present application, the powder after dehydrogenation may be slightly agglomerated or have a changed particle size distribution due to shrinkage, etc., and usually needs to be sieved again or subjected to batch processing to ensure batch uniformity.
[0036] (6) After the TC4 alloy powder is subjected to degassing treatment, it is loaded into a preheated can, and subjected to three-stage temperature control in a vacuum environment. The first stage controls the heating rate to be 5-10°C / min, and the temperature is raised to 150-250°C to remove impurities and slowly extract vacuum to ≤1×10 -2 Pa; the second stage raises the temperature to 400-500°C to further extract vacuum to ≤4×10 -2 Pa; the third stage controls the heating rate to be 3-6°C / min to avoid temperature unevenness, and the temperature is raised to 920-980°C, and a static pressure of 100-140MPa is applied at this temperature range, and the heat preservation and pressure holding time is 120-180min. After heat preservation, under argon medium, first load argon pressure of 45-65KPa, cool to below 450°C at a rate of ≥10°C / min; then load argon pressure of 105-135KPa, continue to cool to room temperature. A preform with a density of ≥99.8% is obtained, and the microstructure is a duplex structure with primary equiaxed α size ≤10μm and α lamellar spacing ≤10μm.
[0037] In one embodiment of the present application, the material of the sheath is pure titanium plate, the size of the sheath is 80-100 mm (thickness) x 1800-2000 mm (width) x 2000-2200 mm (length), the wall thickness of the sheath is 1-3 mm, and the preheating temperature is 400-450 DEG C. The process control curve of hot isostatic pressing is shown in Figure 1 The temperature of hot isostatic pressing is lower than the beta transformation temperature T β (998 DEG C), the holding time is 120-180 min, and after the holding is finished, rapid cooling is performed, the pressure gradient is loaded under argon medium, and the growth of alpha phase is inhibited. The above method has the advantages of avoiding the problem of alpha phase coarsening, improving the density, and improving the powder bonding strength; the pure titanium sheath is used, no demolding treatment is needed, surface oxidation is avoided in the subsequent heating medium; the sheath is contained in rolling, the long process of conventional acid and alkali washing is avoided, and the surface quality is ensured.
[0038] In the present application, in order to solve the problems of poor organization uniformity and low flaw detection qualified rate in the traditional process, powder metallurgy preform is used to replace the traditional ingot. The waste is treated by hydrogenation and dehydrogenation to prepare powder, then the TC4 alloy powder with low oxygen content is prepared by plasma rotating electrode atomization, and then the three-step hot isostatic pressing is used for consolidation to form a bimodal organization preform, which avoids macrosegregation from the source. The high temperature and high pressure environment of hot isostatic pressing promotes powder diffusion bonding, refines grains and eliminates internal defects, and significantly improves material density. Through the method, the ingot dendritic segregation is completely eliminated, the microstructure is refined and high uniformity is achieved, and the aviation level flaw detection requirement is met.
[0039] (7) After the billet is heated to the rolling temperature in a gas atmosphere or an electric heating furnace, the billet is discharged for rolling, one-fire rolling is adopted, and the rolling direction is along the width direction of the preform. The opening rolling temperature of one-fire rolling is 40-80 DEG C higher than the beta phase transformation point of the preform, the subsequent pass temperature is reduced to the alpha+beta two-phase region, and the finish rolling temperature is greater than or equal to 700 DEG C. The principle of rolling deformation rate distribution is that the deformation ratio (beta phase region: alpha+beta two-phase region = 1.1-1.2:1), the total deformation amount is greater than 80%, and the deformation amount of the subsequent passes is gradually reduced to 10-15%. After the finish rolling pass, roller slow cooling is adopted, and the cooling rate is controlled at 1.5-2.0 DEG C / s.
[0040] In the present application, one-fire rolling is adopted instead of traditional multi-fire forging+rolling, high-efficiency deformation is realized by precise temperature control (avoiding harmful phase transformation region), the intermediate heat treatment times are reduced, the yield rate is effectively improved, the process is shortened, and the energy consumption is reduced, thereby solving the problems of low yield rate and high energy consumption caused by long process of traditional process. The preform is contained in rolling, the pure titanium sheath prevents oxidation, the plastic deformation is synchronized with the matrix during rolling, the surface is free of acid and alkali washing, and the surface quality is improved.
[0041] (8) the rolled plate is heated to 780-820 ℃ and held for 1-2 h, AC; then heated to 470-550 ℃ and held for 4-8 h, AC; after cooling, the head and tail are sawn off, and finally the finished plate with a thickness of 5-10 mm, a width of 2000-2200 mm and a length of 6000-15000 mm, and a good surface quality with a basket weave structure is obtained.
[0042] The TC4 plate prepared by the above method has a longitudinal tensile strength of ≥960 MPa, a yield strength of ≥890 MPa, an elongation of ≥13%, a reduction of area of ≥35%, a transverse tensile strength of ≥1000 MPa, a yield strength of ≥960 MPa, an elongation of ≥11%, a reduction of area of ≥35%, a fracture toughness K IC ≥60 MPa·m 1 / 2 , a fracture toughness K IC ≥65 MPa·m 1 / 2 .
[0043] The following specific examples will be listed to explain the scheme of the present application. Those skilled in the art will understand that the following examples are only used to illustrate the present application, and should not be regarded as limiting the scope of the present application. If the specific technology or condition is not specified in the examples, it is carried out according to the technology or condition described in the literature in the art or according to the product instruction. If the reagent or instrument is not specified by the manufacturer, it is a conventional product that can be obtained by purchase.
[0044] The present application provides two groups of TC4 plate prepared by the method of the present application, examples 1-2. In the examples 1-2, the pretreated TC4 recycled waste is used as raw material. The pretreatment method is as follows: after the TC4 recycled waste is cleaned with weak acid (3% HNO3+1% HF solution), vacuum annealing is carried out at 600 ℃ to remove surface impurities. Then the large block of raw material is cut or broken into small blocks with a relatively uniform size of 3-15 mm for standby.
[0045] Example 1 1) The pretreated TC4 raw material is placed in a sealed reactor, high-purity hydrogen is introduced to a pressure of 2.8 MPa, and hydrogenation is carried out at 400 ℃ for 8 h. The brittle TC4 hydride block after hydrogenation is taken out of the reactor, and the brittle hydride is broken into powder by a simple mechanical breaking method. The hydride powder of 3-15 mm is separated by sieving.
[0046] 2) The hydride powder is placed in a vacuum furnace at 650 ℃ and a vacuum degree of ≤10 -2The TC4 alloy powder with an average particle size of 50 μm was obtained by plasma rotating electrode atomization treatment after dehydrogenation of the TC4 alloy powder in a heat treatment furnace of Pa for 18 h and cooling to room temperature in vacuum.
[0047] The TC4 alloy powder was subjected to chemical composition detection, and the mass fractions of main elements were respectively: Al 5.6%, V 4.0%, O 0.06%, H 0.003%, N 0.006%, C 0.012%, and Fe 0.11%.
[0048] 3) After the TC4 alloy powder was subjected to degassing treatment, the powder was loaded into a pure titanium sheath with a size of 80 mm (thickness) × 2000 mm (width) × 2200 mm (length) (the thickness of the sheath titanium plate is 1.0 mm), the sheath preheating temperature is 400 ℃; three-step hot isostatic pressing treatment was carried out in a vacuum environment: in the first stage, the temperature rising rate is controlled to be 5 ℃ / min, the temperature is raised to 150 ℃, and the vacuum is slowly extracted to ≤1 × 10 -2 Pa; in the second stage, the temperature rising rate is controlled to be 5 ℃ / min, the temperature is raised to 400 ℃, and the vacuum is further extracted to ≤4 × 10 -2 Pa, in the third stage, the temperature rising rate is controlled to be 3 ℃ / min, the temperature is raised to 920 ℃, and a static pressure of 140 MPa is applied in the temperature interval, and the holding time is 180 min. After the holding is completed, the argon gas pressure is loaded to 45 KPa, and the temperature is cooled to below 400 ℃ at a rate of 10 ℃ / min; then the argon gas pressure is loaded to 105 KPa, and the temperature is continuously cooled to room temperature, to obtain a duplex structure preform.
[0049] The density of the duplex structure preform is 99.89%, and the microstructure is a duplex structure with a primary equiaxed α size of 8 μm and an α lamellar spacing of 6 μm, and the metallographic structure photograph is shown in Figure 2 .
[0050] 4) One-heat forming is adopted for rolling, and the β phase transformation point of the duplex structure preform is measured to be 1008 ℃. The billet is heated to the rolling temperature in a gas atmosphere or an electric heating furnace, and then is taken out of the furnace for rolling. The opening rolling temperature is 1048 ℃, the final rolling temperature is 700 ℃, and the total deformation amount is 90%. The rolling specification in the early stage of rolling is 60 mm→50 mm→40 mm→30 mm→25 mm→22 mm, the rolling temperature is 1048 ℃~1008 ℃, and the rolling deformation rate is distributed as follows: 63.3% deformation is completed above the β phase transformation point; the rolling specification in the late stage of rolling is 22 mm→19 mm→17 mm→15 mm→13 mm→11.5 mm→10 mm, the rolling temperature is 1008 ℃~700 ℃, and the rolling deformation rate is distributed as follows: 54.5% deformation is completed in the α+β two-phase region below the phase transformation point; the two-phase region deformation ratio is 1.16, and the billet is cooled on a roller after the final rolling pass, and the cooling rate is controlled to be 2.0 ℃ / s.
[0051] 5) The rolled plate is kept at 820 ℃ for 1 h, AC; then kept at 470 ℃ for 8 h, AC, and after cooling, the head and tail are sawn off, to obtain a finished plate of 10 mm (thickness) × 2200 mm (width) × 13400 mm (length) with good surface quality and a microstructure of α lamella in short rod shape and a basketweave structure with α clusters arranged alternately, as shown in Figure 3 .
[0052] The mechanical properties of the TC4 plate prepared by the above method are detected according to GB / T228.1, the longitudinal tensile strength is 970 MPa, the yield strength is 892 MPa, the elongation is 13.3%, the reduction of area is 35.4%, the transverse tensile strength is 1019 MPa, the yield strength is 960 MPa, the elongation is 11.8%, and the reduction of area is 35.7%, the fracture toughness is detected according to GB / T4161, the K IC The measured value is 65 MPa·m 1 / 2 , the K IC The measured value is 70 MPa·m 1 / 2 .
[0053] Example 2 1) The pretreated TC4 raw material is placed in a sealed reactor, high-purity hydrogen is introduced to a pressure of 0.3 MPa, and hydrogenation is carried out at 800 ℃ for 18 h. The brittle TC4 hydride block after hydrogenation is taken out of the reactor, and the brittle hydride is broken into powder by a simple mechanical crushing method. The hydride powder of 3-15 mm is separated by screening.
[0054] 2) The hydride powder is placed in a heat treatment furnace at 820 ℃ and a vacuum degree of ≤10 -2 Pa for 8 h to dehydrogenate. After cooling to room temperature in vacuum, plasma rotating electrode atomization treatment is carried out to obtain TC4 alloy powder with an average particle size of 150 μm.
[0055] Chemical composition detection is performed on the TC4 alloy powder, and the mass fractions of main elements are respectively: Al 5.8%, V 3.9%, O 0.04%, H 0.004%, N 0.005%, C 0.014%, and Fe 0.11%.
[0056] 3) The TC4 alloy powder is degassed and then loaded into a pure titanium sleeve with a size of 100 mm (thickness) × 1800 mm (width) × 2000 mm (length) (the thickness of the titanium plate of the sleeve is 3.0 mm), and the sleeve preheating temperature is 450 ℃. Three-step hot isostatic pressing is carried out in a vacuum environment: in the first stage, the temperature rising rate is controlled at 10 ℃ / min, the temperature is raised to 250 ℃, and the vacuum is slowly extracted to ≤1×10 -2 Pa; in the second stage, the temperature rising rate is controlled at 10 ℃ / min, the temperature is raised to 500 ℃, and the vacuum is further extracted to ≤4×10- 2 Pa, the three-stage control heating rate is 6℃ / min, heated to 980℃, and the temperature interval is applied to 100MPa static pressure, the holding time is 120min. After holding, under argon medium, load argon pressure pressure is 65KPa, to 15℃ / min rate gradient cooling to 450℃ below; then load argon pressure pressure is 135KPa, continue to cool to room temperature, obtain dual state organization preform.
[0057] The density of the dual state organization preform is 99.92%, the microstructure is dual state organization with primary equiaxial α size of 10μm and α sheet spacing of 8μm, and the metallographic structure photograph is shown in Figure 4 .
[0058] 4) rolling adopts one-fire forming, and the β phase transition point of the dual state organization preform is measured to be 1000℃. The billet is heated to the rolling temperature in a gas atmosphere or an electric heating furnace, and then rolled out of the furnace. The opening rolling temperature is 1080℃, and the final rolling temperature is 700℃. The total deformation rate of rolling is 90%. The rolling specification in the early stage of rolling is 100mm→90mm→72mm→58mm→46mm→36mm→28mm→22mm→18mm, the rolling temperature is 1080℃~1000℃, and the rolling deformation rate distribution is that 82% deformation is completed above the β phase transition point. The rolling specification in the late stage of rolling is 18mm→14mm→10mm→7.8mm→6.8mm→5.8mm→5mm, the rolling temperature is 1000℃~700℃, and the rolling deformation rate distribution is that 72.2% deformation is completed in the α+β two-phase region below the phase transition point. The two-phase region deformation ratio is 1.13, and the final rolling pass is cooled on the roller bed at a cooling rate of 1.5℃ / s.
[0059] 5) After rolling, the plate is kept at 780℃ for 2h, and then kept at 550℃ for 4h, AC, and cooled. After sawing off the snake head and tail, the final product plate with a thickness of 5mm, a width of 2080mm, and a length of 6920mm is obtained, which has good surface quality and a net basket structure with α sheet in short rod shape and α bundle staggered arrangement.
[0060] The TC4 plate prepared by the above method has mechanical properties detected according to GB / T228.1, longitudinal tensile strength of 982MPa, yield strength of 899MPa, elongation of 14%, reduction of area of 37%, transverse tensile strength of 1004MPa, yield strength of 958MPa, elongation of 12.5%, and reduction of area of 36.8%. The fracture toughness is detected according to GB / T4161, T-L direction K IC The actual measurement is 62MPa·m 1 / 2 , L-T direction K IC The actual measurement is 69MPa·m 1 / 2 .
[0061] Comparative Example 1: The preform was prepared according to the steps 1) to 3) of Example 1, with the difference that in step 3), the hot isostatic pressing was directly controlled at a heating rate of 6°C / min, and directly heated to 1000°C for holding and pressing, to obtain the preform. The microstructure of the prepared preform is shown in Figure 5 It can be seen that the bimodal microstructure preform cannot be equiaxed, and the microstructure uniformity is poor.
[0062] Comparative Example 2: The finished plate was prepared according to the steps 1) to 5) of Example 1, with the difference that in step 4), the rolling deformation rate distribution in the early stage of rolling was 70.3% deformation above the β phase transformation point, and the rolling deformation rate distribution in the late stage of rolling was 45.5% deformation in the α+β two-phase region below the phase transformation point, and the two-phase region deformation ratio was 1.55, to obtain the finished plate. The microstructure of the prepared finished plate is shown in Figure 6 It can be seen that when the deformation ratio is not in accordance with the rolling deformation rate distribution principle, the single-phase region processing rate is large and the two-phase region deformation is obviously insufficient, the grain boundary α of the plate structure cannot be broken.
Claims
1. A method for producing a TC4 titanium alloy preform, characterized in that: TC4 scrap is pretreated, then is pulverized by hydrogenation and dehydrogenation, and then is treated by plasma rotating electrode atomization to obtain alloy powder with oxygen content of ≤0.15wt%; the alloy powder is treated by three-step hot isostatic pressing to obtain a TC4 titanium alloy preform with a duplex structure; The TC4 titanium alloy preform has a density of ≥99.8%, a primary equiaxial α phase size of ≤10μm, and an α lamella spacing of ≤10μm; The three-step HIP treatment includes: one stage, heating to 150-250℃ at 5-10℃ / min, vacuum extraction to ≤1×10 -2 Pa; two stages, heating to 400-500℃ at 5-10℃ / min, vacuum extraction to ≤4×10 -2 Pa; three stages, heating to 920-980℃ at 3-6℃ / min, applying 100-140MPa static pressure, holding for 120-180min.
2. The method according to claim 1, wherein the pretreatment comprises: cleaning the TC4 scrap with a 3% HNO3 solution and a 1% HF solution, then annealing the TC4 scrap under vacuum at 600-800℃, and then cutting or breaking the TC4 scrap into small pieces with a size of 3-15mm. The TC4 scrap comprises one or more of machining chips, forming excess material, and metallurgical waste.
3. The method according to claim 1, wherein the TC4 alloy powder has a particle size of 50-150μm; and the TC4 alloy powder has element contents other than oxygen content that meet the requirements of GB / T3620.
1.
4. The method according to claim 1, wherein the hot isostatic pressing further comprises: loading the TC4 alloy powder after degassing treatment into a jacket that is preheated to 400-450℃, and then performing three-step hot isostatic pressing; after the hot isostatic pressing, cooling the TC4 alloy powder to below 450℃ at a cooling rate of ≥10℃ / min in an argon environment with a pressure of 45-65KPa, and then cooling the TC4 alloy powder to room temperature in an argon environment with a pressure of 105-135KPa, to obtain the TC4 titanium alloy preform with a duplex structure. The hydrogenation-dehydrogenation powdering comprises: placing small pieces in a closed reactor, introducing high-purity hydrogen to a pressure of 0.3-2.8 MPa, hydrogenating at 400-800 DEG C for 8-18 h, then crushing and sieving to obtain hydride powder; the hydride powder is placed in a vacuum environment with a vacuum degree of less than or equal to 10 -2 Pa, dehydrogenated at 650-820 DEG C for 8-18 h, cooled to room temperature in vacuum or under protection of inert atmosphere, and then subjected to plasma rotating electrode atomization treatment to obtain TC4 alloy powder. The jacket is made of pure titanium plate. The jacket has a wall thickness of 1-3mm. The jacket has a size of: length 2000-2200mm x width 1800-2000mm x thickness 80-100mm. The TC4 titanium alloy preform with a duplex structure is obtained by the method according to any one of claims 1-4, and then is subjected to hot rolling and composite heat treatment to obtain a TC4 titanium alloy plate with a net basket structure. The net basket structure has α lamellas in the form of short rods and α clusters arranged in a staggered manner. The hot rolling is specifically: one-fire rolling is adopted, the preform is heated to a rolling temperature in a gas atmosphere or an electric heating furnace, and then is rolled out of the furnace, the rolling direction is along the width direction of the preform, the opening rolling temperature is 40-80℃ above the β phase transition point of the preform, the temperature of subsequent passes is reduced to the α+β two-phase region, and the final rolling temperature is ≥700℃; the rolling deformation rate distribution principle of the one-fire rolling is that the deformation ratio of the β phase region to the α+β two-phase region is 1.1-1.2:1, the total deformation amount is >80%, and the deformation amount of subsequent passes is gradually reduced to 10-15%. After the final rolling pass of the one-fire rolling, roller slow cooling is adopted, and the cooling rate is controlled at 1.5-2.0℃ / s.
5. A method for producing a TC4 titanium alloy plate, characterized in that:
7. The method according to claim 5, wherein 6. The method of producing a TC4 titanium alloy plate according to claim 5, characterized in that: The complex heat treatment is specifically as follows: heating the rolled plate to 780-820 ℃, holding for 1-2 h, air cooling to room temperature; heating to 470-550 ℃, holding for 4-8 h, air cooling to room temperature; sawing off the head and tail to obtain the TC4 titanium alloy plate with the basket weave structure.
8. A TC4 titanium alloy sheet having a basket weave texture, characterized in that: The TC4 titanium alloy plate is prepared by the preparation method of any one of claims 5-7. 9.The TC4 titanium alloy plate with the basket weave structure according to claim 8, characterized in that: The size of the TC4 titanium alloy plate is 6000-15000 mm in length, 2000-2200 mm in width and 5-10 mm in thickness. 10.The TC4 titanium alloy plate with the basket weave structure according to claim 8, characterized in that: The mechanical properties of the TC4 titanium alloy plate are: longitudinal tensile strength >=960MPa, yield strength >=890MPa, elongation >=13%, reduction of area >=35%; transverse tensile strength >=1000MPa, yield strength >=960MPa, elongation >=11%, reduction of area >=35%; fracture toughness K IC >=60MPa·m 1 / 2 , fracture toughness K IC >=65MPa·m 1 / 2 .
Citation Information
Patent Citations
Preparation method of ultrathin TC4 titanium alloy plate
CN115971249A
Hot rolling preparation method of TC4 titanium alloy single sheet
CN117066281A
Method for rolling thin-gauge ultra-wide TC4 titanium alloy plate through one heating number
CN120079718A
Method for preparing TiAl alloy plate by argon atomization in powder metallurgy
CN102513537A
High-strength plastic titanium-based composite material annular part as well as preparation method and application thereof
CN120394879A